In Vivo Kinetics of mRNA Splicing and Transport in Mammalian Cells - Audibert, A. (American Society for Microbiology, 2002)
The kinetics of pre-mRNA processing in living cells is poorly known, preventing a detailed analysis of the regulation of these reactions. Using tetracycline-regulated promoters we performed, during a transcriptional induction, a complete analysis of the maturation of two cellular mRNAs, those for LT-α and β-globin. In both cases, splicing was appropriately described by first-order reactions with corresponding half-lives ranging between 0.4 and 7.5 min, depending on the intron. Transport also behaved as a first-order reaction during the early phase of β-globin expression, with a nuclear dwelling time of 4 min. At a later time, analysis was prevented by the progressive accumulation within the nucleus of mature mRNA not directly involved in export. Our results further establish for these genes that (i) splicing components are never limiting, even when expression is induced in naive cells, (ii) there is no significant RNA degradation during splicing and transport, and (iii) precursor-to-product ratios at steady state can be used for the determination of splicing rates. Finally, the comparison between the kinetics of splicing during transcriptional induction and during transcriptional shutoff reveals a novel coupling between transcription and splicing.